On the definition of Transnational Corporations in a UN Code of Conduct - Gerd Schetting (Intereconomics, 1980)
The UN Commission on Transnational Corporations which was appointed by ECOSOC will have its next meeting in May. An Intergovernmental Working Group will have held ten sessions by then and present a draft Code of Conduct dealing with transnational corporations. (For a review of the state of preparations for this Code see the article by Hartmut Scheele in INTERECONOMICS No. 6/1979). The Commission itself and the Working Group have dealt more than once with the question to which enterprises the future Code is to apply but they have so far been unable to reach agreement. The difficulties are examined in the following article.
Keywords: 330; Un Code of Conduct